ANALISIS KUALITAS BUTIR SOAL SUMATIF AKHIR SEMESTER MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Agus Rifai; Riski Ramadhan; Miftahir Rizqa (STKIP Subang, 2026)
This study aims to analyze the quality of the Final Semester Summative test items for Islamic Religious Education in 9th grade at SMP Negeri 2 Ukui, looking at aspects of validity, reliability, discriminating power, and difficulty level. The study uses a descriptive quantitative approach. The subjects of the study consisted of 31 9th-grade students, and the instrument used was 50 multiple-choice questions. Data collection was done through documentation of students' answer sheets and test papers, while data analysis was carried out using item analysis calculations with the help of SPSS. The research results show that out of 50 questions, 35 questions are valid and 15 questions are invalid. The reliability test obtained a Cronbach’s Alpha value of 0.912, which falls into the very high category. For the distinguishing power aspect, 14 questions are categorized as very good, 13 questions as good, 16 questions as fair, 6 questions as poor, and 1 question as very poor. Meanwhile, in terms of difficulty level, 40 questions are categorized as easy, 8 questions as medium, and 2 questions as hard. Based on this analysis, it can be concluded that the quality of the End-of-Semester Summative Exam questions for Islamic Religious Education is generally quite good and feasible to use.